Thinking actively in social contexts for improving the creating thinking skills - Rovi Susanto; I Gusti Putu Suryadarma (Research and Social Study Institute, 2019)
The study aims at developing the Thinking Actively in Social Contexts (TASC) and the fit manual book for improving the studentsâ€™ creative thinking skills. Within the conduct of the study, the 4D (Define, Design, Develop and Disseminate) had been adopted. First, the Define stage consisted of curriculum analysis, studentsâ€™ characteristics analysis, studentsâ€™ activities analysis and learning objectives and materials analysis. Second, the Design stage consisted of media selection, manual book format design and preliminary product prototype manufacture. Third, the Develop stage consisted of manual book prototype development with expert judgment and development test (limited experiment and expanded experiment). Fourth, the Disseminate stage consisted of manual book distribution after the manual book had been revised by the given party. Then, the results of the study show that both the TASC learning model and the manual book have been fit for improving the studentsâ€™ creative thinking skills. Based on the post-test results that have been analysed using the gain-score test and the t-test, it might be concluded that the studentsâ€™ creative thinking skills have fallen into the â€œHighâ€ category. In other words, the TASC learning model provides learning opportunity for the students based on the social context of the farming problems.